Importance-Practicability Analysis of NCS-based Vocational Skills among Students in Beauty Specialized High School - Kim, Bobae; Lee, Jaeeun; Chon, Haejung (Asian Journal of Beauty and Cosmetology, 2022)
Purpose: This study aims to strengthen job competency that is effectively used in the beauty industry. By analyzing the importance and performance level of the required basic job skills as per the national competency standards (NCS) of high school students specializing in beauty, job competency can be improved.Methods: A survey was conducted on 158 students enrolled in a specialized beauty high school in Seoul from March 22 to April 20, 2021. Frequency, factor, reliability, correlation, and simple regression analyses were performed. This study also used the importance–practicability analysis (IPA) matrix of basic vocational competency.Result: The IPA analysis results reveal that organizational understanding needs improvement. Moreover, as sub-areas, human resource capability, conflict management, negotiation, and technology application ability were identified, further confirming the urgent need for improvement. In addition, intense investment in this area is required. The higher the perceived social self-efficacy, the better information is provided with the help of others. Moreover, students’ ability to prepare for job search is greater, and the effect on organizational understanding is positive.Conclusion: Previous studies posited that the self-efficacy of university students has a positive effect on organizational understanding ability and confirmed that using the flipped learning teaching method improves the self-efficacy. The use of flipped learning in beauty as a subject, where theory and practical classes are mixed, and self-efficacy is used as a medium to strengthen organizational understanding, it is expected that it will help high school students specializing in beauty to adapt to the industry.